Antarctic Halacaridae (Acari), new records, these species characteristics and an updated list of species - Bartsch Ilse (Polish Polar Research, 2016)
Four halacarid species: Agaue agauoides, Agaue parva, Bradyagaue drygalskii, and Halacarus minor have been extracted from bottom samples taken in Admiralty Bay, King George Island, South Shetland Islands, another four, Colobocerasides auster, Halacarus arnaudi, Lohmannella fukushimai, and L. gaussi, from Kapp Norvegia, Atka and Halley Bay, Weddell Sea. Most of these species are widespread around Antarctica and adjacent islands. Diagnostic characters are outlined. An annotated list presents 66 halacarid species reported from south of the Antarctic Polar Front.